Sustainable Energy Systems Planning, Integration, and Management - Anvari-Moghaddam, Amjad; Mohammadi-ivatloo, Behnam; Asadi, Somayeh; Guldstrand Larsen, Kim; Shahidehpour, Mohammad (Applied sciences, 2019)
The electric power system in a sustainable future will augment the centralized and large-grid-dependent systems of today with distributed, smaller-scale energy generation systems that increasingly adopt renewable energy sources (e.g., solar and wind) and rely on cyber technologies to ensure resiliency and efficient resource sharing. At the supply side, there exists a bunch of opportunities for renewable energy technologies complemented with energy efficiency measures not only to provide local benefits, but also to contribute to sustainable development, which is framed in a three-pillar model: Economy, Ecology, and Society. [...]the relationship between the use of renewables in energy mix and the sustainable developments goals (SDGs) can be viewed as a set of objectives and constraints that involve both global and local/regional considerations. 2. Furthermore, a general enhancement of the wave energy is noticed, and it appears that this enhancement is relatively higher in the western side. [...]related studies showed that the coastal environment of the Black Sea, and especially its northern and western side, is fully appropriate for the implementation of offshore wind projects.